Area and edge effects on leaf-litter decomposition in a fragmented subtropical dry forest - Moreno, Maria Laura (2014)
South American subtropical dry forests are highly threatened by fragmentation. Despite considerable research efforts aimed at predicting ecosystem alterations due to this driver of global change, we still need to deal with general principles to improve our ability to predict the impact of fragmentation. Our work is one of the few studies that analyse the relationship between forest fragmentation and decomposition. In 12 remnants of Chaco Serrano forest in Central Argentina we tested if decomposition rates of a common leaf-litter substrate varied with fragment size and between the forest edge and interior. Decomposition declined with fragment size, with no significant effects of location (edge/interior) or interaction between the two components of fragmentation. Our results suggest that in situ conditions for decomposition may change as a consequence of forest fragmentation, specifically as a result fragment size. This may lead to impaired nutrient recycling in smaller forest remnants.